2015
DOI: 10.1007/s13277-015-3858-4
|View full text |Cite
|
Sign up to set email alerts
|

Introducing differential expression of human heat shock protein 27 in hepatocellular carcinoma: moving toward identification of cancer biomarker

Abstract: Previously, it has to be acknowledged that overexpressed heat shock protein B27 (HSPB27) have been implicated in the etiology of wide range of human cancers. However, the molecular mechanism leading to the disease initiation to progression in liver cancer is still unknown. Present work was undertaken to investigate the differentially expressed HSPB27 in association with those damages that lead to liver cancer development. For the identification of liver cancer biomarker, samples were subjected to comparative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The studies showed that HSP70 is a promising tumor marker for both diagnostic and therapeutic applications [46, 47] . Moreover, several reports showed high levels of Hsp27 in sera of patients with different types of cancers by ELISA [20, 45, 4853]. The studies showed that Hsp27 synthesis was enhanced during the early stages of endometrial cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…The studies showed that HSP70 is a promising tumor marker for both diagnostic and therapeutic applications [46, 47] . Moreover, several reports showed high levels of Hsp27 in sera of patients with different types of cancers by ELISA [20, 45, 4853]. The studies showed that Hsp27 synthesis was enhanced during the early stages of endometrial cancer development.…”
Section: Discussionmentioning
confidence: 99%